Evaluation of the effect of defects on the mechanical performance of components manufactured by selective laser melting - Leuders, S.; Tröster, Thomas; Brenne, F.; Riemer, A.; Richard, H. A.; Niendorf, T.

On the mechanical performance of structures manufactured by selective laser melting: Damage initiation and propagation - Leuders, S.; Tröster, Thomas; Riemer, A.; Richard, H. A.; Niendorf, T.

Reliable communication using Erasure Codes for monitoring bats in the wild - Mutschlechner, Margit; Klingler, Florian; Erlacher, Felix; Hagenauer, Florian; Kiessling, Marcel; Dressler, Falko (2014 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Time-causal material modeling in the simulation of guided waves in circular viscoelastic waveguides - Bause, Fabian; Schroder, Andreas; Rautenberg, Jens; Henning, Bernd; Gravenkamp, Hauke (2014 IEEE International Ultrasonics Symposium)

Unsicherheitsanalyse eines Vorwärtsmodells zur Simulation transienter Wellenausbreitung im Hohlzylinder - Bause, Fabian; Weber, Daniel; Rautenberg, Jens; Henning, Bernd

Model based sensitivity analysis of Leaky-Lamb wave propagation to the variation of viscous lubricant properties - Bause, Fabian; Brückner, Christoph; Miedl, Jens; Henning, Bernd (Beiträge der 17. ITG/GMA-Fachtagung)

Modellgestützte Analyse des Trocknungsverhaltens von Dispersionslacken aus Daten einer NIR-Multidetektoranordnung - Hoof, Christian; Appelhans, Silke; Henning, Bernd
Zur schnellen und berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung ge-nutzt. In dieser Untersuchung wird das Trocknungsverhalten von Dispersionslack auf einem rauen Substrat mit einer Multidetektoranordnung untersucht. Durch diese Anordnung ist es möglich, gerichtete und diffuse Strahlungsanteile zu detektieren, wodurch zeitvariable Glanzeffekte an der Lackoberfläche miterfasst werden. Mit Hilfe eines Raytracing-Algorithmus wird die Trocknung eines Dispersionslackes simuliert und anhand von Messdaten mit einem FTIR-Spekt-rometer verifiziert.

Sensitivitätssteigerung im Rahmen eines inversen Ansatzes zur Materialparameterbestimmung für Piezokeramiken durch Elektrodenmodifikationen - Unverzagt, Carsten; Henning, Bernd
Simulationen mittels der Finiten Element Methode (FEM) sind heute ein fester Bestandteil im Entwicklungsprozess von Ultraschallsystemen. Durch die simulative Ermittlung der transienten Schwingungsvorgänge können Optimierungen bezüglich gewünschter Zielkriterien vorgenommen werden. Hierdurch lassen sich die aufwendige Prototypenfertigung reduzieren und günstige Entwurfspunkte schneller ermitteln.

On the computation of dispersion curves for axisymmetric elastic waveguides using the Scaled Boundary Finite Element Method - Gravenkamp, Hauke; Bause, Fabian; Chongmin, Song (Computers and Structures)

SAT-Based ATPG beyond Stuck-at Fault Testing - Hellebrand, Sybille; Wunderlich, Hans-Joachim (DeGruyter Journal on Information Technology (it))

Adaptive Bayesian Diagnosis of Intermittent Faults - Rodriguez Gomez, Laura; Cook, Alejandro; Indlekofer, Thomas; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing - Theory and Applications (JETTA))

Common Fate Graph Patterns in Monte Carlo Tree Search for Computer Go - Graf, Tobias; Platzner, Marco (2014 IEEE Conference on Computational Intelligence and Games)

Reducing the power consumption of household refrigerators through the integration of latent heat storage elements in wire-and-tube condensers - Sonnenrein, G.; Elsner, A.; Baumhögger, Elmar; Morbach, A.; Fieback, K.; Vrabec, J. (International Journal of Refrigeration)

Apparatus for the measurement of the speed of sound of ammonia up to high temperatures and pressures - Dubberke, Frithjof H.; Rasche, David B.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Prediction methods for pool boiling heat transfer: A state-of-the-art review - Gorenflo, Dieter; Baumhögger, Elmar; Herres, Gerhard; Kotthoff, Stephan (International Journal of Refrigeration)

Mixed methods analysis of enterprise social networks - Trier, Matthias; Behrendt, Sebastian; Richter, Alexander (Computer Networks)

Modeling and inverse identification of a high bandwidth ultrasonic measurement setup based on piezoelectric 1-3 composites - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Modellbasierte inverse Identifikation von Ultraschall-Transducern anhand der elektrischen Eingangsimpendanz - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Mixed methods analysis of enterprise social networks - Behrendt, Sebastian; Richter, Alexander; Trier, Matthias (Computer Networks)

Der richtige Ansprechpartner im dynamischen Interaktionsnetzwerk - Trier, Matthias; Müller, Matthias; Bobrik, Annette (HMD Praxis der Wirtschaftsinformatik)

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Business Intelligence 2.0 - Behrendt, Sebastian; Richter, Alexander; Schäfer, Sebastian; Trier, Matthias (Vernetzte Organisation)

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

Modeling intrinsic defects in LiNbO3 within the Slater-Janak transition state model - Li, Yanlu; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Chemical Physics)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

The set of circular flow numbers of regular graphs - Schubert, Michael; Steffen, Eckhard (J. Graph Theory)

Petersen colorings and some families of snarks - Hägglund, Jonas; Steffen, Eckhard (Ars Mathematica Contemporanea)

PAC Rank Elicitation through Adaptive Sampling of Stochastic Pairwise Preferences - Busa-Fekete, Robert; Szörényi, B.; Hüllermeier, Eyke (Proceedings AAAI 2014, Quebec, Canada)

A Survey of Preference-Based Online Learning with Bandit Algorithms - Busa-Fekete, Robert; Hüllermeier, Eyke (Proceedings Int. Conf. on Algorithmic Learning Theory (ALT), Bled, Slovenia)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (Proceedings Discovery Science, Bled,Slovenia)

The Choquet kernel for monotone data - Fallah Tehrani, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings ESANN , Bruges, Belgium)

Learning Solution Similarity in Preference-Based CBR - Abdel-Aziz, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings Int. Conf. Case-Based Reasoning (ICCBR), Cork, Ireland)

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings Lernen-Wissensentdeckung-Adaptivität (LWA), Aachen, Germany)

Machine Learning and Knowledge Discovery in Databases-European Conf. ECML/PKDD, Nancy, France - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Proceedings, Parts I-III. Lecture Notes in Computer Science)

On Consumer Purchasing Behavior in Electronic Markets - Herrmann, Philipp

Preference Learning (Dagstuhl Seminar 14101) Dagstuhl Reports - Fürnkranz, J.; Hüllermeier, Eyke; Rudin, Cynthia; Slowinski, Roman; Sanner, Scott

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Dependent binary relevance models for multi-label classification - Montanés, E.; Senge, Robin; Barranquero, J.; Quevedo, J.R.; Del Coz, J.J.; Hüllermeier, Eyke (Pattern Recognition)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, Ammar; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Extended Graph-Based Models for Enhanced Similarity Search in Cavbase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Identification of Functionally Releated Enzymes by Learning to Rank Methods - Stock, M.; Fober, T.; Hüllermeier, Eyke; Glinca, S,; Klebe, G.; Pahikkala, T.; Airola, A.; De Baets, B.; Wageman, W. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Adsorption of PTCDA on Terraces and at Steps Sites of the KCl(100) Surface - Guo, Q.; Paulheim, A.; Sokolowski, M.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Oxygen adsorbates on the Si(111)4×1-In metallic atomic wire: Scanning tunneling microscopy and density-functional theory calculations - Oh, Deok Mahn; Wippermann, S.; Schmidt, Wolf Gero; Yeom, Han Woong (Physical Review B)

Geometrical and optical benchmarking of copper(II) guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory (part II) - Hoffmann, Alexander; Rohrmüller, Martin; Jesser, Anton; dos Santos Vieira, Ines; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Formation of Hydroxyl Groups at Calcium-Silicate-Hydrate (C-S-H): Coexistence of Ca–OH and Si–OH on Wollastonite(001) - Sanna, Simone; Schmidt, Wolf Gero; Thissen, Peter (The Journal of Physical Chemistry C)

Rashba splitting and relativistic energy shifts in In/Si(111) nanowires - Gerstmann, Uwe; Vollmers, N. J.; Lücke, A.; Babilon, M.; Schmidt, Wolf Gero (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Design of an Electrical Interferometer at 120 GHz for Contactless Permittivity Characterization - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Scheytt, Christoph (Elektrotechnisches Kolloquium)

Architectural Low-Power Design Using Transaction-Based System Modeling and Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))
Energy efficiency drives the development of more and more complex low-power designs. Based on dynamic power management techniques, multiple voltage islands as well as a huge amount of power states are specified that have to be tested carefully. In this context, low-power design should start at an early stage using state-of-the-art system-level modeling and simulation techniques. However, there is neither a programming language nor any modeling standard that reflects variable power together with its functional side effects in a well-suited abstract manner. To overcome this limitation, we present a modeling approach on top of SystemC TLM to capture low-power design characteristics at electronic system-level. We demonstrate the usability by means of an existing open-source low-power design. The experimental results show that appropriate TLM instrumentation cause only minimal simulation overhead, but offer sufficient details to identify common low-power design errors.

Switchable slow wave transmission line in 130 nm SiGe technology at 115 GHz for phase detection based biosensors - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik (Microwave Symposium (IMS), 2014 IEEE MTT-S International)
A 115 GHz slow wave transmission line intended for phase detection based integrated biosensors is presented. The structure was fabricated in a 130 nm SiGe process. It achieved the targeted overall phase shift of 1° at 115 GHz. Moreover, the phase can be adjusted by 16 switches using Heterojunction Bipolar (HBT) transistors leading to a phase resolution of 0.125°. The change in input and output matching over all configurations of the switches is not higher than 0.8 dB and the transmission S 21 varies with less than 0.7 dB. To the authors knowledge, it is the first switchable slow wave structure using microstrip transmission lines along with a bipolar switch circuitry. Moreover, the presented structure provides a very powerful solution for real-time digital read-outs in integrated biosensors, without need of additional signal processing steps.

A 7 GHz biosensor for permittivity change with enhanced sensitivity through phase compensation - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik; Cahill, Brian (European Microwave Conference (EuMC))
A calibration technique as well as measurement results for a 7 GHz Biosensor are presented. It is shown that the applied sensor structure can be calibrated by adjusting the phase of a sensing element's transmission S21. This is realized by slowing down the wave traveling a microstrip line serving as a reference in the differential sensor structure. The dielectric properties along with certain physical boundaries of an obstacle covering parts of the microstrip line evoke that effect. Measurements with an ethanol serious along with simulation results showed that sensitivity can be increased substantially with this calibration technique. A change of the real part of the sample's permittivity of 48 leads to a 18 MHz frequency shift.

Wireless 100 Gb/s: PHY layer Overview and Challenges in THz freqency band - Kraemer, Rolf; Wolf, Andreas; Scheytt, Christoph; Kallfass, Ingmar; KrishneGowda, Karthik (2014 IEEE 15th Annual IEEE Wireless and Microwave Technology Conference (WAMICON))
There is a continuous increase of bandwidth-demanding services such as ultra HDTV, 3D TV, etc. which will require data rates up to 100-400 Gb/s for short range wireless communication. This paper introduces a novel mixed-mode design where both analog and digital domain design is considered, which helps in the reduction of power consumption. Parallel Sequence Spread Spectrum (PSSS) is used for physical layer (PHY) baseband technology, which considerably alleviates both transmitter and receiver design.

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Scheytt, Christoph (Design and Verification Conference (DVCON EUROPE))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.

Verific-MM: Systematized Verification Metrics Generation with UCIS for Improved Automation on Verification Closure - Kuznik, Christoph; Müller, Wolfgang (Design, Automation and Test in Europe DATE, University Booth, Dresden)
Verific-MM is an approach to systematize and accelerate the coverage plan engineering as well as the verification environment’s (functional) metric code generation -- usually a time-consuming and error-prone task -- in particular by (i) improving automation via assisted model-based approaches, utilizing recent industry standards such as UCIS and (ii) a supporting methodology suitable for various target (functional coverage) languages (IEEE-1800 SystemVerilog, IEEE-1647 e, IEEE-1666 SystemC).

System-on-Chip Design für Funkfrequenzen oberhalb von 100 GHz-Herausforderungen und potenzielle Anwendungen - Scheytt, Christoph (Analog 2014,14. Fachtagung der Gesellschaft für Mikroelektronik, Mikrosystemtechnik und Feinwerktechnik des VDE und VDI)

A -Band Four-Element Butler Matrix in 0.13 µm SiGe BiCMOS Technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Scheytt, Christoph; Ellinger, Frank (IEEE JOURNAL OF SOLID-STATE CIRCUITS)

Safety Evaluation of Automotive Electronics Using Virtual Prototypes: State of the Art and Research Challenges - Oetjens, Jan-Hendrik; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Bannow, Nico; Brinkmann, Oliver; Burger, Andreas; Chaari, Moomen; Chakraborty, Samarjit; Drechsler, R.; Ecker, Wolfgang; Grüttner, Kim; et al. (Design Automation Conference (DAC))
Intelligent automotive electronics significantly improved driving safety in the last decades. With the increasing complexity of automotive systems, dependability of the electronic components themselves and of their interaction must be assured to avoid any risk to driving safety due to unexpected failures caused by internal or external faults. Additionally, Virtual Prototypes (VPs) have been accepted in many areas of system development processes in the automotive industry as platforms for SW development, verification, and design space exploration. We believe that VPs will significantly contribute to the analysis of safety conditions for automotive electronics. This paper shows the advantages of such a methodology based on today's industrial needs, presents the current state of the art in this field, and outlines upcoming research challenges that need to be addressed to make this vision a reality.

Logik und Metaphysik - Ficara, Elena (Hegel – 200 Jahre Wissenschaft der Logik. Deutsches Jahrbuch für Philosophie)

Hegel on the Mathematical Infinite - Ficara, Elena (Siegener Beiträge zur Geschichte und Philosophie der Mathematik)

Hegel's Glutty Negation - Ficara, Elena (History and Philosophy of Logic)

Real-time capable methods to determine the magnet temperature of permanent magnet synchronous motors—A review - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (IECON 2014-40th Annual Conference of the IEEE Industrial Electronics Society)

Determination of rotor temperature for an interior permanent magnet synchronous machine using a precise flux observer - Specht, Andreas; Wallscheid, Oliver; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014-ECCE ASIA))

Testing the relationship between income inequality and life expectancy: A simple correction for the aggregation effect when using aggregated data - Mayrhofer, Thomas; Schmitz, Hendrik (Journal of Population Economics)

Broke, ill, and obese: is there an effect of household debt on health? - Keese, Matthias; Schmitz, Hendrik (Review of Income and Wealth)

Regional variation in the utilisation of ambulatory services in Germany - Kopetsch, Thomas; Schmitz, Hendrik (Health Economics)

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Das Erkenntnisproblem und die Mathematik. Zum Streit zwischen dem Marburger Neukantianismus und dem Neofriesianismus - Peckhaus, Volker (Wissenschaftsphilosophie im Neukantianismus. Ansätze – Kontroversen – Wirkungen)

Unsinn und Chance eines Fiktionalismus in der Logik - Peckhaus, Volker (Fiktion und Fiktionalismus. Beiträge zu Hans Vaihingers Philosophie des Als Ob)
Rezension: Zeitschrift für philosophische Forschung 69 (2015), 614–615 (Thomas Uebel)

Ernst Schröder on Pasigraphy (Dossier de la logique philosophique à la logique mathématique) - Peckhaus, Volker (Revue d’histoire des sciences)
Rezension: Math. Rev. MR3330648 (L.G. González); Zbl. Math. 1315.01023 (T.-L. Rădulescu)

In memoriam Helmar Frank

Effects of a mass finishing process on parts produced from Ultem 9085 by Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (ANTEC)
Parts produced by Fused Deposition Modeling (FDM) tend to have rough and undulating surfaces with staircase effects on rounded and slanting areas of the part. This is due to the characteristics of the process. In many fields of application, high demands are made on the optical quality of the part. An improvement in the surface quality of FDM parts made of Ultem*9085 can be achieved through post-treatment with a mass finishing process. In this paper, FDM specimens are post-treated in a disk finishing unit. Influences of the mass finishing process are analyzed with regard to the dependence of surface quality on the various process parameters and on the finishing medium, grinding time and grinding speed. The finishing efficiency depends on the finishing media and decreases for lower finishing time. For all media a lower disk velocity results a smaller grinding effect, but there are clearly differences between the finishing media. The paper also discusses effects of the grinding process on the mechanical properties of the parts. Especially small part geometries and parts build in z-direction tend to break during the finishing process.